THE PHARMACEUTICO- ANALYTICAL STUDY OF OLEAGINOUS FORMULATION: ARJUNA GHRITA (International Journal of Ayurveda and Pharma Research, 2016)
Ayurvedic literature have a lot of unexplored or least tested medicines, Arjuna Ghrita is such one indicated for all types of cardiac disorder. As the incidences of cardiac disorder are increasing, need of a drug like Arjuna ghrita which could be used in many diseases should be formulated. Till date no work has been done at pharmaceuticoanalytical study of Arjuna ghrita. It is an oleaginous formulation needed to be explored in scientific light. Preparation of oleaginous dosage form is described as Sneha kalpana done by subjecting Ghrita or oil to a particular a pattern of heat treated with different Kalka (paste) and liquid media like Kwath (decoction). Murchhana is a pre-procedure to Sneha kalpana in which Ghrita is treated with few drugs. Three samples of Arjuna ghrita were prepared from three different brand cows ghee following the classical texts. Obtained samples were unctuous, viscous soft mass of yellow color with slightly bitter taste and characteristic bitter odour and its analytical study was done. In analytical study calculated mean value for refractive index is 1.456, specific gravity is 0.9181, iodine value is 31.026, saponification value is 131.13, peroxide value is 1.5 and acid value is 1.02. Assay of heavy metals and microbial contamination were under prescribed limit for samples of Arjuna ghrita. Therefore the values obtained can be considered as standard for Arjuna ghrita.